2006
DOI: 10.1007/s10508-006-9092-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Scripts of Women: A Longitudinal Analysis of Participants in a Gender-Specific HIV/STD Prevention Intervention

Abstract: Project FIO (The Future Is Ours) was a three arm randomized controlled HIV prevention intervention trial carried out with heterosexually-active women in a high sero-prevalence area of New York City. The trial was effective and women in the eight-session intervention arm were significantly more likely to report decreased unsafe sex or no unsafe sex compared to controls at one month and one year post-intervention. The current investigation was a qualitative analysis of women's sexual scripts at baseline and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Consistent with previous theoretical and empirical research on AA women and substance-using women, we found that the majority of women utilized sexual scripts that aligned with high risk sex [59,70,73,75] as 56.67% reported adoption of sexual scripts that included condomless sex with sexual partners. Themes found reflect the major dimensions of sexual scripts identified by Bowleg et al These scripts correlate with cultural values placed on maintaining a male partner and support the principles posed by Wingood et al in the application of the TGP to cultural norms and sexual behaviors of AA women as it relates to perceived partner infidelity by the male partner [44][45][46]65,[95][96][97].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with previous theoretical and empirical research on AA women and substance-using women, we found that the majority of women utilized sexual scripts that aligned with high risk sex [59,70,73,75] as 56.67% reported adoption of sexual scripts that included condomless sex with sexual partners. Themes found reflect the major dimensions of sexual scripts identified by Bowleg et al These scripts correlate with cultural values placed on maintaining a male partner and support the principles posed by Wingood et al in the application of the TGP to cultural norms and sexual behaviors of AA women as it relates to perceived partner infidelity by the male partner [44][45][46]65,[95][96][97].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies to date explored sexual scripts of AA women [36,49,54,55,59,72,73,75,77,94]. To our knowledge, this is the first study to move beyond the description of sexual scripts to identify and describe factors that are likely along the pathway to sexual script development among YSSAAW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite women's automatic association between sex and submission, researchers have found evidence that women can learn to be more sexually assertive (Dworkin et al 2007), which may be particularly helpful for women who more strongly associate sex with submission, as they tend to experience the most sexual problems ). This research is promising because it indicates that sexual behaviors, desires, and fantasies are potentially malleable and therefore people can be proactive in developing a sexuality that is safe, satisfying, and representative of their authentic selves.…”
Section: Implications Of Submissive Sexual Fantasy Preferencementioning
confidence: 99%
“…Social script and symbolic interactionist theory has been used by many researchers to explore the way in which individuals negotiate safer sex within broader cultural discourse about sexual identity, gender and sexual practice (Dolan and Davis 2003, Dworkin, Beckford, and Ehrhardt 2007, Giffin 1998, Lear 1995, Mutchler 2000. Mutchler (2000), for example, observes that public campaigns for safer-sex have influenced dominant sexual scripts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%